Improvement in quality of cow’s raw milk by using novel on-farm milk cooling system: Raw milk cooling system - Vekariya, Yogeshkumar; Patel, Dr. Sunil; Kathiriya, Mital (Indian Journal of Dairy Science, 2023)
The present study was conducted with an aim to check the improvement in raw milk quality at farm level by novel milk cooling system. Bulk milk cooler was taken as control. Optimization of different precooling temperatures viz., 30°C, 20°C, 10°C and 4°C in novel milk cooling system was carried out based on microbial and physicochemical tests. The raw milk samples were stored at 4°C and analyzed at an interval of 24 h for 72 h. Significant (p<0.05) reduction in the aerobic plate count and psychrotrophic count was observed when precooling temperature was decreased from 30°C to 10°C whereas non-significant difference was observed when precooled at 10°C and 4°C. The aerobic plate count and psychrotrophic counts of the raw milk samples ranged from 5.02±0.16 log CFU/ml to 6.87±0.17 log CFU/ml and 1.71±0.13 log CFU/ml to 3.54±0.17 log CFU/ml, respectively throughout the storage period. Whereas, pH and titratable acidity of cow’s milk samples ranged from 6.71±0.04 to 6.56±0.08 and 0.14±0.01%LA to 0.16±0.02%LA, respectively throughout the storage period. pH and titratable acidity of all milk samples during storage at 4°C for 72 h remained non-significant. Among the treatments, raw milk precooled at 10°C and 4°C showed lower aerobic plate count and psychrotrophic count with non-significant difference, hence, precooling of raw milk was optimized to 10°C. The better quality of raw milk can be obtained at reduced operating expenses using such novel milk cooling system. The farmers can earn higher incentives from superior quality of raw milk.